Theoreical Aspects of Enterprise Competitiveness Estimation - Верясова, Г. М.; Аль-Фахор, С. С. (ХНУРЕ, 2020)
Дана робота присвячена вивченню терміна «конкурентоспроможність підприємств». Також було визначено, що конкурентоспроможність компанії залежить від таких факторів: конкурентоспроможність товарів на внутрішньому та зовнішньому ринках, тип вироблених товарів, розмір ринку, легкий доступ до ринку, конкурентоспроможність галузі, конкурентна позиція компаній, можливість технологічних інновацій у галузі, конкурентоспроможність регіону та країни. The given work is devoted to the study of term «enterprise competitiveness». It was also determined that company’s competitiveness depends on the following factors: competitiveness of goods on domestic and foreign markets, the type of manufactured goods, market size, easy access to the market, competitiveness of the industry, the competitive position of companies, the possibility of technological innovations in the industry, competitiveness of the region and country.
Keywords: сompetitiveness; method of determining the competitivenesі; enterprise